2021
DOI: 10.4317/medoral.24155
|View full text |Cite
|
Sign up to set email alerts
|

Are mucous retention cysts and pseudocysts in the maxillary sinus a risk factor for dental implants? A systematic review

Abstract: Background Mucous retention cysts and pseudocysts of the maxillary sinus are benign lesions present in up to 13% of adult patients. Different surgical approaches for sinus lift and dental implant placement in the presence of these lesions have been proposed. Material and Methods A systematic review was performed following the PRISMA statement recommendations to answer the PICO question: Does the aspiration or removal of mucous retention cysts/pseudocysts before or durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 32 publications
1
31
0
1
Order By: Relevance
“…Since most of the recommended approaches are based on case reports, there is no research-based consensus. Anitua et al 8 reported a systemic review examining whether cysts should be removed before or during a sinus lift. This study included 182 people with previous mucous retention cysts or pseudoantral cysts in 195 maxillary sinuses where 233 implants were installed.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Since most of the recommended approaches are based on case reports, there is no research-based consensus. Anitua et al 8 reported a systemic review examining whether cysts should be removed before or during a sinus lift. This study included 182 people with previous mucous retention cysts or pseudoantral cysts in 195 maxillary sinuses where 233 implants were installed.…”
Section: Discussionmentioning
confidence: 99%
“…No statistical differences in implant survival were observed in relation to age, sex, surgical approach, implant surgery, or grafting material. They concluded that the presence of mucous retention cysts or pseudoantral cysts had not been considered a contraindication for sinus lift and implant placement and that removal of the cysts did not affect implant survival 8 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations